An XPA gene splicing mutation resulting in trace protein expression in an elderly patient with xeroderma pigmentosum group A without neurological abnormalities. (19th May 2017) - Takahashi, Y.; Endo, Y.; Kusaka‐Kikushima, A.; Nakamaura, S.; Nakazawa, Y.; Ogi, T.; Uryu, M.; Tsuji, G.; Furue, M.; Moriwaki, S.
Summary: A certain relationship between XPA gene mutations and the severity of symptoms has been observed in patients with xeroderma pigmentosum group A (XP‐A). Patients with mutations within the DNA‐binding domain usually exhibit severe symptoms, whereas splicing mutations in the same domain sometimes cause very mild symptoms. This inconsistency can be explained by a small amount of functional XPA protein produced from normally spliced transcripts. We herein report the case of an adult Japanese patient with XP‐A with unusually mild symptoms. We identified a homozygous c.529G>A mutation in exon 4 of the XPA gene, which resulted in aberrant splicing with a 29‐bp deletion in exon 4 causing a frameshift. Intact mRNA was observable, but a Western blot analysis failed to detect any normal XPA protein. We therefore evaluated the DNA repair capacity in normal cells in which the XPA expression was artificially diminished. The repair capacity was still present in cells with trace levels of the XPA protein. The repair capacity of the cells derived from our patient with mild symptoms was poor by comparison, but still significant compared with that of the cells derived from a patient with XP‐A with severe symptoms. These results provide strong evidence that a trace level of XPA protein can still exert a relatively strong repair capacity, resulting in only a mild phenotype. Abstract : Linked Comment: Dawe and McGuire. Br J Dermatol 2017;177 :21–22